Aspiration Pneumonia in Children with Cerebral Palsy after Videofluoroscopic Swallowing Study - Lagos-Guimarães,Hellen Nataly Correia (2016)
Abstract Introduction Dysphagia is a common symptom in children with cerebral palsy, either in oral or pharyngeal phases. Children who face such difficulties tend to show health problems such as food aspiration, malnutrition and respiratory infections. Videofluoroscopic swallowing study is the most recommended for these cases, as it reveals the real situation during swallowing. Objective The study aimed to verify the occurrence of aspiration pneumonia in children with cerebral palsy after videofluoroscopy. Methods The population for this prospective cross-sectional study involved 103 children with cerebral palsy, referred for videofluoroscopic who had returned for medical examination after a week to search for signs and symptoms of pneumonia. Results The study involved 46 girls (44.66%) and 57 boys (55.34%), aged between 0 and 14 years of age. Of the total, 84 (81.5%) had dysphagia, of which 24 (23.3%) were severe, 8 (7.7%) were moderate and 52 (50.4%) were mild dysphagia. None of the children presented aspiration pneumonia or infectious complications during the course of videofluoroscopy or after the procedure. Conclusion In the population studied, the authors found no cases of aspiration pneumonia, even with tracheal aspiration present in 32 (31.07%) cases.